From “Grand Principles” to “Lived Stories”: An Autoethnography of Narrative Transformation Among University Student Affairs Workers - Song, Shulin (Journal of Educational Research and Policies, 2025)
Based on the consideration that educational narratives by student affairs workers in higher education institutions can be an effective pathway for their professional growth, this study focuses on the practical application of educational narratives by these workers. Using autoethnographic analysis to return to real-life contexts, it summarizes and outlines the characteristics of their educational narratives. The research traces the transformation of these narratives—from the professional journey of “explaining principles”, “demonstrating rationale”, and “debating their merits” to the workplace “epiphanies” of “narrating stories about ‘being a person’”, “narrating stories about ‘being a teacher’”, and “narrating stories about ‘handling matters’”. Through this analysis, the study provides insights into the professional development of student affairs workers and offers a case study on how they can maintain the appropriate intensity and rhythm of educational narratives in the digital-intelligent era.